Waterlogged wood remains found in a Late Bronze Age settlement (Inonü Cave) on the Western Black Sea coast of Türkiye - Yaman, Barbaros; Ekmen, Hamza; Yaman, Barbaros (Elsevier, 2023)
The remains of wooden structures belonging to the Late Bronze Age were unearthed during the excavations carried out in the Ino center dot nu Cave, which is located approximately 25 km inside the Eregli district of Zonguldak, on the western Black Sea coast of Turkiye. Thanks to the special conditions of the cave, the woods that makes up the structures that have survived until today has been examined within the scope of this study. All wood flooring elements examined in this study consist of water-filled wood, except for one example (NNDK-1), which has semi-water-filled properties. In the construction of the wooden floor, one oak species from the white oak group (probably Quercus petraea (Matt.) Liebl.) and one pine species from the Sylvestris group (probably Pinus nigra Arnold), Alnus glutinosa (L.) Gaertner and Acer L. sp. were used. In addition, the most used genus in its construction was oak (Quercus L., section Quercus). The inhabitants of Inonu cave in the Late Bronze Age must have met their wood needs from nearby local resources. Wood anatomical analysis pointed out the occurrence of riverine forests formed by Black alder along the streams and temperate broadleaf and mixed forests formed by Sessile oak, maple, and Black pine in Inonu cave and its vicinity. These, together with others like Fagus orientalis Lipsky, Carpinus betulus L., Carpinus orientalis Mill., Salix alba L., and Populus nigra L., are the genera/species present in the region today.
Keywords: Archaeobotany; Ino Center Dot Nu Cave; Late Bronze Age; Waterlogged Wood; Wood Anatomy; Wood Identification; Canti Technique